Tough, adhesive biomimetic hyaluronic acid methacryloyl hydrogels for effective wound healing - Peng, Zhiwei; Xue, Huai; Liu, Xiao; Wang, Shuguang; Liu, Guodong; Jia, Xinghai; Zhu, Ziqiang; Orvy, Moontarij Jahan; Yang, Yin; Wang, Yunqing; Zhang, Dong; Tong, Lei (Frontiers in Bioengineering and Biotechnology, 2023)
Development of cost-effective, biocompatible soft wound dressings is highly desirable; however, conventional dressings are only designed for flat wounds, which renders difficulty with promising healing efficiency in the complex practical conditions. Herein, we developed a tough, adhesive biomimetic hyaluronic acid methacryloyl hydrogels composed of chemically crosslinked hyaluronic acid methacryloyl (HAMA) network and poly(N-hydroxyethyl acrylamide) (PHEAA) network rich in multiple hydrogen bonding. Due to the multiple chemical crosslinking sites (acrylamide groups) of HAMA, the bulk HEMA/PHEAA hydrogels presented significant enhancements on mechanical properties (~0.45 MPa) than common hyaluronic acid hydrogels (<0.1 MPa). The abundant hydrogen bonding also endows the resultant hydrogels extremely high adhesiveness on many nonporous substrates, including glass and biological tissues (e.g., heart liver, lung, kidney, stomach, and muscle), with a considerable interfacial toughness of ~1432 J m −2 . Accordingly, since both natural hyaluronic acid derivative polymers and hydrophilic PHEAA networks are highly biocompatible, the hydrogel matrix possesses good blood compatibility (<5% of hemolysis ratio) and satisfies the general dressing requirements (>99% of cell viability). Based on these physicochemical features, we have demonstrated that this adhesive hydrogel, administered in the form of designed patch, could be applied to wound tissue healing by promoting epithelialization, angiogenesis, and collagen deposition. We believe that our proposed biomimetic hydrogel design holds great potential for wound repair and our developed HAMA/PHEAA hydrogels are extremely promising for the next-generation tissue healings in emergency situations.